A novel 6.3 kb deletion and the Rare 27.6 kb Deletion Causing α+-Thalassemia in two Chinese Patients. (2nd September 2016) - Wang, Xian-Yao; Lin, Ming-Xiang; Lin, Min
Abstract: We report a novel –α 6.3 deletion and a rare –α 27.6 deletion causing α + -thalassemia (α + -thal), in two Chinese patients. One patient was a 35-year-old Chinese man with a mild α + -thal phenotype [mean corpuscular volume (MCV) 83.6 fL] and the Hb A2 level (2.5%) was close to borderline of the normal range. Multiplex ligation-dependent probe amplification (MLPA) revealed a novel 6344 bp deletion involving the entire HBA1 gene. Mapping by gap-polymerase chain reaction (gap-PCR) defined the exact breakpoint of this deletion to be NG_000006.1: g.31022_37366del6344. It was unique relative to other forms of α-thalassemia (α-thal) reported in the literature, and was designated as –α 6.3 deletion. The other patient, a 41-year-old woman had Hb H (β4) disease [hemoglobin (Hb) level of 8.9 g/dL] with a compound heterozygosity for the – – SEA (NG_000006.1: g.26264_45564del19301) deletion. The MLPA and gap-PCR methodologies confirmed the breakpoint (NG_000006.1: g.9079_36718del27640) and identified it as the rare –α 27.6 deletion.